EEC syndrome: A rare case management - Payel Agarwala; Krittika Samaddar; Chitradeep Chakraborty; Sudipta Kar; Shabnam Zahir (Wolters Kluwer Medknow Publications, 2022)
Ectrodactyly-ectodermal dysplasia-cleft lip/palate (EEC) syndrome is a rare congenital anomaly. Infants affected with this syndrome experience feeding difficulties due to the presence of orofacial clefts, which in turn impedes nutrition and affects overall health. Due to the presence of oronasal communication in such infants, there is a lack of negative pressure necessary for suckling. Due to the cleft lip, these infants face trouble closing their mouths around the nipple of the mother or bottle and due to the cleft palate, the infants suffer from choking and nasal regurgitation during feeding due to the inability of the palate to separate the oral and nasal cavities. A feeding appliance is a crucial aid because it obturates the cleft and creates a platform against which the infant can press the nipple and extract milk until the cleft is surgically repaired. However, conventional feeding plates may be potentially dangerous due to the risk of accidental swallowing. Furthermore, the wire component of certain feeding appliances may cause tissue injury. KRIPA's feeding appliance incorporates an adjustable head strap and Polyvinyl chloride (PVC) tube-enclosed retentive hooks which render it safer and more acceptable. This case report represents the fabrication of KRIPA's feeding appliance for a 3.5-month-old infant with EEC syndrome.